The Remarkable Plasticity of Macrophages: A Chance to Fight Cancer - Nadège Bercovici; Nadège Bercovici; Nadège Bercovici; Marion V. Guérin; Marion V. Guérin; Marion V. Guérin; Alain Trautmann; Alain Trautmann; Alain Trautmann; Emmanuel Donnadieu; Emmanuel Donnadieu; Emmanuel Donnadieu (Frontiers in Immunology, 2019)
It is well established that tumor-associated macrophages (TAM) found in most advanced tumors have a pro-tumoral role. In this context, TAM limit the activity of tumor-infiltrating lymphocytes (TIL), and a number of mechanisms have been described including a trapping in the stroma, impeding TIL to reach malignant cells. Based on these results, a number of therapeutic approaches have been designed to deplete TAM. However, during tumor regression induced by immunotherapeutic treatments, recent studies revealed that TAM can switch from pro-tumoral to anti-tumoral and actively cooperate with TIL. Here, we will review the two faces of TAM in their interaction with TIL. We will summarize how they can inhibit T cell activities in growing tumors, and how they may also, together with T cells, successfully contribute to tumor eradication after an appropriate stimulation. Finally, we will discuss current promising therapies combining TAM reprogramming with T cell-based immunotherapy.